PENDIDIKAN KESEHATAN TENTANG CARA MENJAGA SISTEM IMUN TERHADAP PERUBAHAN IKLIM PADA SISWA MAN 1 MUARA BUNGO - Nurcihikita, Tiara; Wibowo, Hendry; Hidayat, Husnil; Ikhsani, Khoirun (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
Climate change is increasingly impacting public health, including the heightened risk of diseases due to changing weather patterns and air quality. This study aims to measure the effectiveness of health education in enhancing the knowledge of students at MAN 1 Muara Bungo regarding adaptation efforts related to climate change. The sample consists of 50 individuals, including mentors and students actively involved in scout activities. The results indicate a significant increase in students' knowledge after participating in the health education sessions, with the average score rising from 44.463 to 54.33. These findings suggest that health education based on healthy lifestyle practices can be an effective intervention in improving community preparedness, particularly among the youth, to face health challenges posed by climate change.